Utilization of Aloe vera Plants as a Raw Materials for Cosmetics: A Narrative Review - Tasya Salsabila; Wanda Indriyani; Sari, Yanita; Nia Yuniarsih (HM Publisher, 2022)
One of the plants that can be used as natural ingredients in cosmetics is aloe vera (Aloe vera). Aloe vera is very easy to get and has also been widely cultivated in Indonesia. The benefits of aloe vera are very diverse, including as an antibiotic, antiseptic, antibacterial, antiviral, anti-infective, anti-inflammatory, and anti-swelling. Aloe vera is effective in replacing damaged cells and improving skin conditions because there are polysaccharides that work together with essential amino acids and protein-breaking enzymes. Other aloe vera content in vitamins A, B12, E, inositol, and folic acid. The mineral content includes calcium (Ca), magnesium (Mg), potassium (K), sodium (Na), iron (Fe), zinc (Zn), and chromium (Cr). Aloe vera can be used as cosmetic preparations in the form of hair tonic, lotion, lip balm, shampoo, creambath, and liquid soap.